If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
x+6/3 = 3*x // - 3*x
x-(3*x)+6/3 = 0
x-3*x+6/3 = 0
2-2*x = 0 // - 2
-2*x = -2 // : -2
x = -2/(-2)
x = 1
x = 1
| 3*-4*x+7=15 | | 6(x-3)=3(2x+9)-9 | | 6x2/3-216=0 | | 80-20(3)/5= | | s=ut+0.5at*at | | 3x+5x=-2 | | -3(x+3)=-3(x+1) | | 5(3t-4)+4t=40-t | | 3p-1=5(p-1)-2(7-9p) | | -3(x+3)=-3(x-1)-5 | | 2/3(9b-27) | | -6(9r+5)= | | 72/3=3x/3 | | 8a-2=38 | | 6+12r-3=9r+93-7r | | 3(x+1)=2(x-1)+6 | | 10-w=90 | | 3x-5=2x-6 | | 3(x-2)+4x=10-x | | 4sin2x-5=0 | | -1(7x)-6(-7-x)=36 | | 2x+40=8 | | 6(4x-8)=3(12x+6) | | |40-7x|=15 | | 6-4(3a-2)= | | 0.50x+0.35(50)=44.5 | | 7x-(3x+9) | | 7d-3c-d= | | 3a^2+4a=21 | | 3x-6=--6 | | 7x+4+8x+6 | | 23-9p=18-4p |